Betulinic Acid Derivative BA5, Attenuates Inflammation and Fibrosis in Experimental Chronic Chagas Disease Cardiomyopathy by Inducing IL-10 and M2 Polarization - Meira, Cássio Santana; Santos, Emanuelle De Souza; Santo, Renan Fernandes do Espírito; Vasconcelos, Juliana Fraga; Orge, Iasmim Diniz; Nonaka, Carolina Kymie Vasques; Barreto, Breno Cardim; Caria, Alex Cleber Improta; Silva, Daniela Nascimento; Barbosa-Filho, José Maria; Macambira, Simone Garcia; Moreira, Diogo Rodrigo Magalhães; et al. (Frontiers in Immunology, 2019)
Chronic Chagas disease cardiomyopathy (CCC) is a major cause of heart disease in Latin America and treatment for this condition is unsatisfactory. Here we investigated the effects of BA5, an amide semi-synthetic derivative betulinic acid, in a model of CCC. Mice chronically infected with T. cruzi were treated orally with BA5 (10 or 1 mg/Kg), three times per week, for 2 months. BA5 treatment decreased inflammation and fibrosis in heart sections but did not improve exercise capacity or ameliorate cardiac electric disturbances in infected mice. Serum concentrations of TNF-α, IFN-γ, and IL-1β, as well as cardiac gene expression of pro-inflammatory mediators, were reduced after BA5 treatment. In contrast, a significant increase in the anti-inflammatory cytokine IL-10 concentration was observed in BA5-treated mice in both tested doses compared to vehicle-treated mice. Moreover, polarization to anti-inflammatory/M2 macrophage phenotype was evidenced by a decrease in the expression of NOS2 and proinflammatory cytokines and the increase in M2 markers, such as Arg1 and CHI3 in mice treated with BA5. In conclusion, BA5 had a potent anti-inflammatory activity on a model of parasite-driven heart disease related to IL-10 production and a switch from M1 to M2 subset of macrophages.